2012
DOI: 10.1016/j.cellimm.2012.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor mediated suppression of natural killer cell activity: Identification of associated deacetylase and corepressor molecules

Abstract: Physical and psychological stressors reduce natural killer cell function. This reduction in cellular function results from stress-induced release of glucocorticoids. Glucocorticoids act upon natural killer cells to deacetylate and transrepress immune response genes through epigenetic processes. However, other than the glucocorticoid receptor, the proteins that participate in this process are not well described in natural killer cells. The purpose of this study was to identify the proteins associated with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 47 publications
1
35
0
1
Order By: Relevance
“…The mechanism by which mental dysfunction acts on NK cells is still debated. Many hypotheses are proposed, including the deregulation of the hypothalamic/pituitary/adrenal axis leading to elevated levels of blood glucocorticoids, which further inhibit NKCA through epigenetic processes (75). Several other mental disorders are correlated with a diminution of NK cell functions, such as obsessive-compulsive disorder (76) and autism (77).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…The mechanism by which mental dysfunction acts on NK cells is still debated. Many hypotheses are proposed, including the deregulation of the hypothalamic/pituitary/adrenal axis leading to elevated levels of blood glucocorticoids, which further inhibit NKCA through epigenetic processes (75). Several other mental disorders are correlated with a diminution of NK cell functions, such as obsessive-compulsive disorder (76) and autism (77).…”
Section: Nk Cell Modifications Associated With Cns Disordersmentioning
confidence: 99%
“…48 The basic immune model of Folcik et al 38 was also extended to include the hormonal actions of CORT and TEST. CORT is a potent modulator of immune function suppressing NK cell activity, 49 Th1 activity, 50 and inflammatory DC activity. 51 Additionally, CORT acts on naïve T-cells to repress both the Th1 promoting transcription factor, T-bet, and the Th2 promoting transcription factor, GATA-3.…”
Section: Literature-based Immune Signaling Networkmentioning
confidence: 99%
“…Human NK cells have also been shown to proliferate in response to a [17]. In contrast, a recent study demonstrated GR-mediated inhibition of NK cell activity [18]. Moreover, it has been shown that GCs disregulate NK cell functions through epigenetic modification [19].…”
Section: Introductionmentioning
confidence: 99%